2023
DOI: 10.1108/raf-01-2022-0020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of short sale prospect on income smoothing

Abstract: Purpose The purpose of this paper is to examine the impact of short sale prospect on future income smoothing. Design/methodology/approach This study examines how short sale prospect impacts future income smoothing. This study follows prior research and uses two measures of income smoothing. One is the correlation between the change in prediscretionary income and the change in discretionary accruals. The other is the variability of earnings relative to the variability of cash flows. Findings This study find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The primary feature of Industry 4.0 is the application of digital technology in the manufacturing sector. Manufacturing enterprises can leverage the positive role of employees to drive digital transformation (Sun et al, 2023) and emphasise employees' contribution to digital transformation. Employees' innovative behaviour and autonomy can help manufacturing enterprises achieve their goal of digital transformation by using their resources and advantages (Helian, 2023).…”
Section: Employee Empowerment and Digital Transformation In Manufactu...mentioning
confidence: 99%
“…The primary feature of Industry 4.0 is the application of digital technology in the manufacturing sector. Manufacturing enterprises can leverage the positive role of employees to drive digital transformation (Sun et al, 2023) and emphasise employees' contribution to digital transformation. Employees' innovative behaviour and autonomy can help manufacturing enterprises achieve their goal of digital transformation by using their resources and advantages (Helian, 2023).…”
Section: Employee Empowerment and Digital Transformation In Manufactu...mentioning
confidence: 99%
“…In this regard, prior research that investigated the implications of SSL on firms found that short-sellers search actively for unfavourable information, can track firms' discretionary accruals, specify earnings manipulation practises and fraud before they are publicly shown, help uncover aggressive earnings management and financial misrepresentation, curb income smoothing, and accelerate the detection of misrepresentation (Sun and Zhang, 2023;Hirshleifer et al, 2011;Karpoff and Lou, 2010;Cao et al, 2007;Desai et al, 2006;Efendi et al, 2005;Christophe et al, 2004;Dechow et al, 1996). So, SSL can be an efficient monitoring mechanism to positively affect the financial reporting quality and mitigate the manager's ability to manage earnings.…”
Section: Introductionmentioning
confidence: 99%